2021
DOI: 10.21203/rs.3.rs-709844/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Menstrual Hygiene Practice among Adolescent Girls in Ethiopia: a systematic review and meta-analysis

Abstract: Background: Adolescent girls face several challenges relating to menstruation and its proper management. Lack of adequate sanitary products, inadequate water supply, and privacy for changing sanitary pads continue to leave adolescent girls with limited options for safe and proper menstrual hygiene in many low-income settings, including Ethiopia. These situations are also compounded by societal myths, stigmas surrounding menstruation, and discriminatory social norms. This systematic review and meta-analysis a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…31 Bleeding during or after sex can be alarming, especially if the mothers were not menstruating. 32 The most likely causes include a sexually transmitted infection, benign polyps, cervical ectropion, atrophic vaginitis, endometriosis, trauma, and cancer. 33 The results suggest that to prevent precancerous cervical lesions one must consider changes of lifestyle and sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…31 Bleeding during or after sex can be alarming, especially if the mothers were not menstruating. 32 The most likely causes include a sexually transmitted infection, benign polyps, cervical ectropion, atrophic vaginitis, endometriosis, trauma, and cancer. 33 The results suggest that to prevent precancerous cervical lesions one must consider changes of lifestyle and sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…7 Alterations in hormones during puberty initiate the transformation of a girl into a sexually mature woman, which is accompanied by psychological, cognitive, and physical changes. 8 Better appreciation and attitude towards menstruation are achieved when the adolescent girl knows about menstruation. 7 Many adolescent girls, particularly in rural regions, lack access to basic information about menstruation and related hygiene practices, and frequently join their menarche without preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inadequate information about bodily changes and a lack of body confidence have been observed in adolescent students, and many have expressed a demand for menstrual health education [16]. Similar studies have reported the existence of little information on menstrual health and menstruation among the majority of adolescent girls [16,17], with most girls viewing menstruation simply as the ability to give birth and perceiving bathing as difficult during menstruation. They also reported considering it inappropriate for girls to talk about their bodies [18].…”
Section: Introductionmentioning
confidence: 99%